EFFECTS OF COMPETITIVE STRATEGIES ON ORGANIZATIONAL PERFORMANCE OF TELECOMMUNICATION COMPANIES IN MOGADISHU- SOMALIA - Mohamed, Jama Abdi; GICHINGA, DR LUCY GICHINGA (IJRDO - Journal of Applied Management Science, 2018)
The telecommunications business in Somalia, as many other countries in the world has in the recent past been among the most competitive industry of the economy. Initially there were only two players but the entry of two other operators made the industry very competitive. Consequently, the growing competitive environment led to price wars which lead to the prices being the lowest in Africa. The firms employ various competitive strategies to survive in the industry. Whether these strategies facilitate them in achieving this and even making the firms more effective. In Somalia Six main companies provide telecommunication services in the country. These include Hormuud Telecom, Telecom Somalia, Telesom, Somafone, Nationlink, and Golis Telecom. They provides a range of products and services which include Land-line,GSM, roaming services, top-up services, data messaging, MMT, voice services, and security services, 3G, GPRS and much more. These services are all geared towards growth and competition. They uses a lot of strategies to gain sustained competitive advantage, however The general objective of this  study was to examine effect of competitive strategies on organizational performance of telecommunication companies in Mogadishu, Somalia. More specifically the study investigated the effects of cost leadership, differentiation, market focus strategies and strategic alliances on organizational performance of telecommunication companies in Mogadishu, Somalia. The researcher used theories of competitive strategies like porter‟s generic strategies and employed a descriptive research design to undertake the study. The population of the study was the top, middle and first line managers of Hormuud telecom Somalia. Data was collected from a sample of 184 respondents using stratified sampling method. A structured questionnaire was used as a research instrument. Both descriptive and inferential statistics was used to analyze data with the help of software called Statistical Package for Social Sciences (SPSS) version 20.0. Standard multiple regression analysis was conducted for hypotheses testing while stepwise multiple regression analysis was conducted in order to establish the best combination of independent (predictor) variables would be to predict the dependent (predicted) variable and to establish the best model of the study. Results confirm the varying importance of the competitive strategies on organizational performance in telecommunication industry in Mogadishu Somalia. In general, the results reveal that all cost leadership strategy and differentiation strategy have significant and positive effects on dependent variable (organizational performance).While focus strategy and strategic alliances have insignificant effect on organizational performance in the mobile telecommunication companies in Mogadishu Somalia. The study recommends that to improve the organizational performance the managers of the telecommunication companies in Mogadishu Somalia should nurture and develop cost leadership strategy and differentiation strategy.